Differential Protein Expression Analysis of Two Sugarcane Varieties in Response to Diazotrophic Plant Growth-Promoting Endophyte Enterobacter roggenkampii ED5 - Guo, Dao-Jun; Li, Dong-Ping; Singh, Rajesh Kumar; Singh, Pratiksha; Sharma, Anjney; Verma, Krishan K.; Qin, Ying; Khan, Qaisar; Lu, Zhen; Malviya, Mukesh K.; Song, Xiu-Peng; Xing, Yong-Xiu; et al. (Frontiers in Plant Science, 2021)
Plant endophytic bacteria have many vital roles in plant growth promotion (PGP) such as nitrogen (N) fixation and resistance to biotic and abiotic stresses. In this study, the seedlings of sugarcane varieties B8 (requires a low concentration of nitrogen for growth) and GT11 (requires a high concentration of nitrogen for growth) were inoculated with endophytic diazotroph Enterobacter roggenkampii ED5, which exhibits multiple PGP traits, isolated from sugarcane roots. The results showed that the inoculation with E. roggenkampii ED5 promoted the plant growth significantly in both sugarcane varieties. 15N detection at 60 days post-inoculation proved the strain ED5 inoculation increased the total nitrogen concentration in leaf and root than control in both sugarcane varieties, which was higher in B8. Biochemical parameters and phytohormones in leaf were analyzed at 30 and 60 days after inoculation. The results showed that the inoculation with E. roggenkampii ED5 improved the activities of superoxide dismutase (SOD), catalase (CAT), NADH-glutamate dehydrogenase (NADH-GDH), glutamine synthetase (GS) and endo-β-1,4-glucanase, and the contents of proline and IAA in leaf, and it was generally more significant in B8 than in GT11. TMT labeling and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to perform comparative proteomic analysis in sugarcane leaves at 30 days after strain ED5 inoculation. A total of 27508 proteins were detected and 378 differentially expressed proteins (DEPs) were found in the treated sugarcane variety B8 (BE) as compared to the control (BC), of which 244 were up-regulated and 134 down-regulated, respectively. Whereas in GT11, a total of 177 DEPs were identified in the treated sugarcane variety GT11 (GE) as compared to the control (GC), of which 103 were up-regulated and 74 down-regulated. The DEPs were associated with nitrogen metabolism, photosynthesis, starch, sucrose metabolism, response to oxidative stress, hydrolase activity, oxidative phosphorylation, glutathione metabolism, phenylpropanoid metabolic process, and response to stresses in GO and KEGG database. To our knowledge, this is the first proteomic approach to investigate the molecular basis of interaction between N-fixing endophytic strain E. roggenkampii ED5 and sugarcane.